PENERJEMAHAN UU NO. 1 TAHUN 2013 TENTANG LEMBAGA KEUANGAN MIKRO: METODE DAN STRATEGI PENERJEMAHAN - Pamungkas, Muhammad Ersan Pamungkas (Kementerian Sekretariat Negara Republik Indonesia, 2014)
This article deals with the topic on problems and challenges in translating Law Number 1 of 2013 on Microfinance Institution. The law contains provisions on the services of microfinance and its institutions. Problems and challenges in the translation process include translating economic terms, as well as methods and strategies to be applied. Based on the result of the research, it can be concluded that the translation process applies Faithful Method and Idiomatic Method. Translating thislegal text also applies several translation strategies. In translating a law, the translation should not only be accurate but also have the function and purpose of the original text.